Socio-Ecological Dynamics of Deforestation Induced by the Influx of Rohingya:: Evidence from Ukhia, Cox’s Bazar, Bangladesh - Khan, Nahreen Islam; Rasel, Mohammad (The Jahangirnagar Review, 2025)
Cox’s Bazar district of Bangladesh is mainly significant in terms of environmental and economic perspective which have been disrupted considerably due to Rohingya influx in 2017. A significant amount of the forest has been cleared for the Rohingya community’s refuge. The appearing deforestation of the mega camp (camps in Kutupalong area) and huge anthropogenic activity has made it necessary to perform a change detection research in this area. The concept of this research comes from the intention to explore the changes it had experienced in past few years. This study inspected the changes with particular reference to a major theoretical approach named Socio-Ecological System since it incorporates an encroachment of a society and the local environment. The overall aim of this research was to find the changes of forest cover in Rohingya response camp area of Ukhia upazila between 2017 to 2022 using Landsat imageries of the study area. In this secondary data-based quantitative research, Normalized Difference Vegetation Index (NDVI) will be performed on three multi-temporal satellite imageries and total of 4 major land cover classes were identified and mapped followed by inspecting interconnectivity between society and environment. The result of this study revealed the amount of deforestation occurred in this area along with the environmental and societal disruption. The findings analyzed and quantified trends of land cover change in the chosen area. The findings were also be used to quantify the patterns of land cover change in the chosen area and analyze land cover changes within a spatiotemporal framework. This can be used as inputs to land management and policy decisions with regard to varied themes that have link with space such as tourism, water management, deforestation and land degradation.